2009
DOI: 10.1007/s10457-009-9209-y
|View full text |Cite
|
Sign up to set email alerts
|

Coarse root growth of Veronese poplar trees varies with position on an erodible slope in New Zealand

Abstract: Poplars are commonly planted on moist, unstable pastoral hill country to prevent or reduce soil erosion, thereby maintaining hillslope integrity and pasture production. Mechanical reinforcement by poplar root systems aids slope stabilisation, particularly when the roots are anchored into the fragipan or underlying rock. Total root length, mass and distribution of coarse roots (C2 mm diameter) were determined for three Populus deltoides 9 nigra 'Veronese' trees in their 12th growing season after being planted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 42 publications
0
27
1
Order By: Relevance
“…They also reported that the maximum coarse root biomass was found in the top 30 cm of the soil profile. In a study by Faulkner [28] the root system of a Euro-American poplar clone was found between 5 and 20 cm below ground level and in a study of 12-year-old Veronese poplar (Populus deltoides × nigra) stands in New Zealand most of the coarse roots (≥2 mm) were found within the top 40 cm of the soil profile [29].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the maximum coarse root biomass was found in the top 30 cm of the soil profile. In a study by Faulkner [28] the root system of a Euro-American poplar clone was found between 5 and 20 cm below ground level and in a study of 12-year-old Veronese poplar (Populus deltoides × nigra) stands in New Zealand most of the coarse roots (≥2 mm) were found within the top 40 cm of the soil profile [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Poplar, few studies like, Puri et al (1994), Fang et al (2007) and McIvor et al (2009) explored 0.3 m, 1.0 m and 1.4 m depth, respectively. However, in the present study, excavation was extended to 3.0 m depth since roots were observed up to 2.4 m to 2.8 m during coring.…”
Section: Root Harvesting Depthmentioning
confidence: 99%
“…Contrary to this, these two varied with change in direction as well in the present study (Populus euramericana I-214). Although Smith (2001) and Kalliokoski et al (2008) observed strong assumption of symmetrical dimension of root system, Puri et al (1994) and McIvor et al (2009) recorded highly asymmetric roots in poplar and other species owing to the effect of non-symmetrical mechanical stress and heterogeneous nutrient availability in soil (Coutts et al, 1999;Casper et al, 2003).…”
Section: Root Orientation and Growthmentioning
confidence: 99%
“…With changing research emphases and enhanced funding in sustainable land management and related areas over the last decade, the distribution and other characteristics of roots of poplar and willow, and factors that influence them, have been determined (McIvor et al, 2005(McIvor et al, , 2009Douglas et al, 2010a, b;Marden and Phillips 2011). On a research farm near Palmerston North, the distribution of coarse/structural roots (> 2 mm diameter) of young trees of Populus deltoides x nigra 'Veronese' (diameter at breast height (DBH) < 30 cm) of different age and size , and position on a slope prone to shallow landslides (McIvor et al, 2009), was determined by whole-tree excavation.…”
Section: Recent Studiesmentioning
confidence: 99%
“…On a research farm near Palmerston North, the distribution of coarse/structural roots (> 2 mm diameter) of young trees of Populus deltoides x nigra 'Veronese' (diameter at breast height (DBH) < 30 cm) of different age and size , and position on a slope prone to shallow landslides (McIvor et al, 2009), was determined by whole-tree excavation. The trees were established by planting 3 m poles (vegetative cuttings), the usual establishment method for this species (Wilkinson 1999), on an east-facing slope of 15-25 o .…”
Section: Recent Studiesmentioning
confidence: 99%